2001
DOI: 10.1126/science.1059175
|View full text |Cite
|
Sign up to set email alerts
|

Using Selective Withdrawal to Coat Microparticles

Abstract: We report a method that uses the process of selective withdrawal of one fluid through a second immiscible fluid to coat small particles with polymer films. Fluid is withdrawn through a tube with its orifice slightly above a water-oil interface. Upon increasing the flow rate, there is a transition from a state where only oil is withdrawn to a state where the water, containing the particles to be coated and appropriate prepolymer reagents, is entrained in a thin spout along with the oil. The entrained particles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 15 publications
1
103
0
Order By: Relevance
“…Another technique waiting to be used for porous particle production is called selective withdrawal [251][252][253][254][255]. Reported initially by Nagel et al [251], the bottom liquid, which is going to be the dispersed phase, is withdrawn just from the interface by a tube where the continuous phase liquid is on top (Fig.…”
Section: Other Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another technique waiting to be used for porous particle production is called selective withdrawal [251][252][253][254][255]. Reported initially by Nagel et al [251], the bottom liquid, which is going to be the dispersed phase, is withdrawn just from the interface by a tube where the continuous phase liquid is on top (Fig.…”
Section: Other Techniquesmentioning
confidence: 99%
“…Reported initially by Nagel et al [251], the bottom liquid, which is going to be the dispersed phase, is withdrawn just from the interface by a tube where the continuous phase liquid is on top (Fig. 23).…”
Section: Other Techniquesmentioning
confidence: 99%
“…However, related geometries have been studied. Spherical particles can be coated by a viscous, dense liquid as they rise under the action of the buoyancy force through the interface with a second, less viscous and less dense liquid [21,22]. Buoyancy forces have been used to coat particles when particles of a lesser density travel from one liquid to another liquid [23].…”
Section: Liquid Entrainmentmentioning
confidence: 99%
“…Recently, several research groups have reported synthesis of polymer particles in microfluidic reactors (Cohen et al 2001;Dendukuri et al 2005;Jeong et al 2005;Lewis et al 2005;Loscertales et al 2002;Nie et al 2005Nie et al , 2006Nisisako et al 2004;Seo et al 2005aSeo et al , 2005bTakeuchi et al 2005;Utada et al 2005;Xu et al 2005;Zhang et al 2006). The syntheses included a two-step process: (1) microfluidic emulsification of monomer or polymeric fluids, and (2) subsequent in-situ (on chip) solidification of the droplets by means of polymerization, gelation, or solvent evaporation.…”
Section: Introductionmentioning
confidence: 99%